Spontaneous activity, conduction velocity and segmental origin of different classes of thoracic preganglionic neurons projecting into the cat cervical sympathetic trunk - Boczek-Funcke, Ansgar; Dembowsky, Klaus; Häbler, Heinz-Joachim; Jänig, Wilfrid; Michaelis, M. (Journal of the autonomic nervous system, 1993)
Previously, in the anesthetized cat, thoracic preganglionic neurons projecting to the superior cervical ganglion were divided into four classes (groups I-IV) by way of their reflex pattern [4, 5]. Neurons of each class are probably involved in a distinct function, such as regulation of peripheral vascular resistance, regulation of blood flow through skin, regulation of pupil diameter, etc. Here it was tested whether the functionally different classes of thoracic preganglionic neurons also differ in the distribution of their segmental origin, their spontaneous activity and the conduction velocity of their axons. The segmental distribution of preganglionic neurons was almost identical to that determined previously with tracer methods. Distinct classes of neurons had different, although overlapping segmental distributions. Most group III neurons were located in segments T1 and T2, whereas group I, II and IV neurons showed a broader distribution. The subpopulations of preganglionic neurons did not differ in their rate of spontaneous activity. No significant difference was found in segmental distribution between neurons with spontaneous activity and silent neurons. No correlation was found between conduction velocity and spontaneous activity. The proportion of unmyelinated units was greater among group I (16.3%), group II (24.1%) and group IV (22.2%) neurons than among group III neurons (8%). The distributions of conduction velocity were significantly different between group I and group III and between group II and group III neurons. Axons of preganglionic neurons located in segments T1 and T2 conducted faster than axons of neurons located more caudally. The present study shows that distinct subpopulations of preganglionic neurons, as defined by their reflex patterns, differ in their segmental location within the spinal cord and with respect to the conduction velocity of their axons.
Elektronische Reproduktion der Druck-Ausgabe 18. März 2003
Gesehen am 21.10.2024